`Dances in the manner of the other people` and the way of educating minority cultures in Laos. - Jaehnichen, Gisa (Cultural Centre University of Malaya & National Department for Culture and Arts, 2013)
Dancing in the manner of the other people requires at least some knowledge on the otherness of those people’s culture. In Laos, the other people are subsumed under the title “sonphau”, which means “tribes” or – with some good will – “people”. Using the term sonphau competes with the politically standardised use of classified names for people living on the top of the mountains “lao sun”, living in the high valleys “lao theung” and living in the lowlands “lao lum”. These terms avoid the peoples’ names to support a down levelled national emphasis that excludes historical and social differences. Thus cultural elements of various meanings can be instrumentalized easily. In the era of developing mass media, performing arts such as dance, theatre and music are the first to become standardized and re-interpreted items of an abstract national whole degrading local dance and music praxis as kind of strange particularities. “Nationalised” dances, which are a lively part of most of the cultures found in Laos, summarize the imagination of the majority’s Lao dance educators assisted by state cultural managers about dances of the minorities living in the mountains and high valleys. One creation is the following very popular dance, which is among others frequently performed on the main stage of the National Cultural Hall. The dancers themselves, in this case graduates from the National School for Dance and Music in Vientiane, are not familiar with dance practices and conceptions of all the different minorities that might be included.